4CPS-071 Therapeutic drug monitoring and safety of high-dose amikacin in critically ill patients. (2nd March 2018) - Barcelo, J; Fernández-Sala, X; Marin-Casino, M; Grau, S
Abstract : Background: Pharmacokinetic parameters are altered in critically ill patients, such as an increase in volume of distribution of hydrophillic drugs. Peak plasma levels of amikacin, a concentration-dependent antibiotic, could be reduced in critically ill patients. Therefore, current recommendations include higher doses of amikacin (above 20 mg/kg/day) in critically ill patients in order to achieve therapeutic plasma levels, which means a possible higher incidence of adverse events, such as nephrotoxicity and ototoxicity. Therapeutic drug monitoring (TDM) and pharmacist intervention can be necessary in this type of patient to prevent these adverse effects. Purpose: To assess the impact of TDM in critically ill patients receiving high-dose amikacin. Results: Material and methods: Retrospective descriptive study performed in a 400-bed tertiary hospital. Data from patients receiving above 20 mg/kg/day amikacin between January 2014 to August 2017 were included. Patients with a glomerular filtration rate (GFR) below 40 ml/min or receiving renal replacement therapy were excluded. An intermediate level (10 hour post-administration) was used to extrapolate almost all peak and trough levels. Peak levels above 50 mcg/ml and trough levels above 1 mcg/ml were considered supratherapeutic. Data collected: demographic, body mass index (BMI), SOFA score (first 24 hours of amikacin therapy), sepsis, dosage, data extraction levels, renal function (values of serum creatinine (SCr) and GFR the first 24 hours of amikacin therapy and worst values during amikacin therapy) and TDM recommendation. Categorical variables were presented as percentages, continuous variables as median and Q1 to Q3 values. Conclusion: Greater number of patients with current recommendation of high doses of amikacin presented supratherapeutic plasma levels of amikacin, and about 70% of patients needed a dose reduction or an interval increase. Therapeutic drug monitoring after first dose should be a regular practice in critically ill patients, whom present an early decline in renal function during amikacin therapy. No conflict of interest